UPAYA PENINGKATAN NILAI EKONOMIS PRODUK UMKM MELALUI SOSIALISASI BISNIS DIGITAL DI DESA CILANGKARA - Kurniawan, Tri Bagus; Ash Shabah, Musyaffa Amin; Rahmawati, Rafika; Khoiriyah, Ummi (An-Nizam, 2024)
Technological developments, especially in digital business, have had a positive impact on Micro, Small and Medium Enterprises (MSMEs) in rural areas, such as Cilangkara Village. Even though the growth trend of internet users in Indonesia shows a significant increase, observations and interviews show that the majority of village residents have not shown sufficient interest in entrepreneurship, especially in facing current developments. In this context, the community service program by Islamic University 45 Bekasi students aims to provide education and increase village residents' interest and skills in entrepreneurship, especially by implementing digital business. Implementation methods, such as observation, outreach and training, are expected to stimulate interest and provide support to village residents, including providing business tools to MSMEs that are not yet running. Digital business education is the key to increasing the competitiveness of MSMEs and driving economic potential at the local level, as is being pursued through community service activities in Cilangkara Village. The latest evaluation shows an improvement in the quality of life of the community, especially among MSMEs in Cilangkara Village, through increasing operational capabilities of digital applications for analysis, marketing and product production. It is hoped that the success of this program will be a sustainable first step to improve and produce MSMEs that are able to compete and develop along with the times.